2018
DOI: 10.15837/ijccc.2018.3.3044
|View full text |Cite
|
Sign up to set email alerts
|

Latent Semantic Analysis using a Dennis Coefficient for English Sentiment Classification in a Parallel System

Abstract: Abstract:We have already survey many significant approaches for many years because there are many crucial contributions of the sentiment classification which can be applied in everyday life, such as in political activities, commodity production, and commercial activities. We have proposed a novel model using a Latent Semantic Analysis (LSA) and a Dennis Coefficient (DNC) for big data sentiment classification in English. Many LSA vectors (LSAV) have successfully been reformed by using the DNC. We use the DNC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We showed that the use of terms overlaps and the traditional statistics based on tf-idf analysis in an individual manner (without semantic investigation) failed to remove a reasonable portion of the text (CR = 68%, only 32% from the text is removed). And in [17,19,20,21,22,29,45], the authors showed that the semantic analysis of the text using a powerful semantic analyzer such the LSA increases the accuracy but the time complexity was the challenge. Therefore, the proposed MLS method draws a map on which kind of text analysis should be used for each part of the text.…”
Section: Build Up a Framework Of The Text Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…We showed that the use of terms overlaps and the traditional statistics based on tf-idf analysis in an individual manner (without semantic investigation) failed to remove a reasonable portion of the text (CR = 68%, only 32% from the text is removed). And in [17,19,20,21,22,29,45], the authors showed that the semantic analysis of the text using a powerful semantic analyzer such the LSA increases the accuracy but the time complexity was the challenge. Therefore, the proposed MLS method draws a map on which kind of text analysis should be used for each part of the text.…”
Section: Build Up a Framework Of The Text Analysismentioning
confidence: 99%
“…Other statistical techniques used to extract semantically related sentences in a document are the LSA [17,19,20,21,29,45] and the Neural Network [12,23,24,25,56]. Different Neural Network (NN) methods have been used to extract summaries from the text document.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations